2020
DOI: 10.3390/ijms21207675
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Differentially Regulates TLR4-Mediated Inflammatory Responses in Early or Late Phases

Abstract: Toll-like receptor 4 (TLR4) signaling is an important therapeutic target to manage lipopolysaccharide (LPS)-induced inflammation. The transcription factor signal transducer and activator of transcription 3 (STAT3) has been identified as an important regulator of various immune-related diseases and has generated interest as a therapeutic target. Here, we investigated the time-dependent roles of STAT3 in LPS-stimulated RAW264.7 macrophages. STAT3 inhibition induced expression of the pro-inflammatory genes iNOS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 102 publications
(113 reference statements)
1
19
0
1
Order By: Relevance
“…Crosstalk between JAK/STAT and TLR pathways has been suggested in several reports ( 45 47 ). In the case of macrophages, STAT3 has been reported to be a negative regulator for TLR4 signaling ( 47 ). Therefore, we concluded that STAT3 signaling plays a role in negatively regulating the inflammatory genes downstream of the TLR pathway in skin epithelial cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Crosstalk between JAK/STAT and TLR pathways has been suggested in several reports ( 45 47 ). In the case of macrophages, STAT3 has been reported to be a negative regulator for TLR4 signaling ( 47 ). Therefore, we concluded that STAT3 signaling plays a role in negatively regulating the inflammatory genes downstream of the TLR pathway in skin epithelial cells.…”
Section: Discussionmentioning
confidence: 92%
“…This report found that STAT3 signaling negatively regulates the expression of genes controlled by the TLR pathway in skin epithelial cells. Crosstalk between JAK/STAT and TLR pathways has been suggested in several reports (45)(46)(47). In the case of macrophages, STAT3 has been reported to be a negative regulator for TLR4 signaling (47).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, including interleukins (ILs), interferons (IFNs), and hematopoietic growth factors, activate the Janus kinase signal transducer and activator of transcription (JAK/STAT) pathway to elicit downstream effects in responding cells. According to their structural features, CISH is associated with cytokine signaling [ 25 ] acting as an important role in development, differentiation, and function of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, STAT3 has already attracted attention of researchers as an important therapeutic target in several diseases. A number of studies have also shown the importance of STAT3 in the inflammatory response to diseases as well as immune response such as inducing pro-inflammatory gene cyclooxygenase 2 expression to regulate TLR4-mediated inflammation in early and late phases, accelerating the development of colitis by the deficiency of STAT3 in hematopoietic cells leads, and involving in the inflammatory bowel disease and bacterial infections [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between JAK/STAT and TLR pathways has been suggested in several reports (45)(46)(47). In the case of macrophages, STAT3 has been reported to be a negative regulator for TLR4 signaling (47). Therefore, we concluded that STAT3 signaling plays a role in negatively regulating the inflammatory genes downstream of the TLR pathway in skin epithelial cells.…”
Section: Discussionmentioning
confidence: 54%